Finite Element Prediction Model of Surface Temperature Rise Based on Fractal Theory (Journal of Fiber Bioengineering and Informatics, 2015)
The prediction of surface temperature induced by frictional heating is of significance for evaluating theserious thermal wear, erosion and lubrication failure for industrial application and design. Temperatureprediction model was established with two steps. Local temperature was calculated firstly with the realcontact area based on the fractal analysis. Then, the finite element prediction model were establishedwith the above value of local temperature, on the basis of wavelet finite element. Finally, the wholetemperature of the fractal engineering surface were demonstrated and simulation results were shown.Moreover, orthogonal simulations were conducted to study the influence of the input parameters offractal dimension, fractal characteristic length and material thermal properties. Results with differentcases demonstrated that all the temperature decreased gradually from the contact surface to the bottomand the temperature increased with the rise of heat transfer properties, fractal dimension and fractalcharacteristic length for the same position. However, heat transfer properties had the most obviousinfluence on the temperature rise, and the following one was fractal dimension.